The relationship between past exercise behavior and future exercise adherence: A sequential mediation analysis. Issue 18 (17th September 2022) - Rodrigues, F.; Figueiredo, N.; Teixeira, D.; Cid, L.; Monteiro, D.
ABSTRACT: The present study explored the mediation role of past exercise adherence, self-reported frequency and intentions in the association between past experience and future exercise adherence. In total, 431 exercisers (female = 216; male = 215) aged 18 and 64 years, engaged in fitness activities such as group fitness classes and resistance training, were included in the analysis. Serial mediation procedures were employed to examine the direct, indirect, and total indirect effects among variables. The predictor variable and all mediators displayed a positive and significant association with future six-month adherence. Past six-month exercise adherence displayed the most significant association with future six-month adherence. The sequential indirect path from exercise experience → past six-months adherence → self-reported frequency → intentions future six-months adherence displayed a positive and significant effect (β = .19 [CI95% = .09, .31]), presenting a partial mediation effect. Past behaviour is the most significant predictor of future adherence, and thus interventions should be based on promoting consistent exercise frequency. Professionals working in the fitness centre context can identify possible dropouts based on their past behaviour and intentions to be physically active in the future.